Pemetaan IT Governance Berdasarkan COBIT 2019 pada Arsitektur Enterprise System Smart Tourism PT. YoY Manajemen Internasional - Haslan Hammanur; Irfan A P; Musyirifah Musyirifah (Universitas Nusa Cendana, 2022)
YoY Manajemen Internasional (YMI) is a development and management company for Sharia-based hotels with its address at Komp. BTN Paropo, Blk. B No.1, Paropo, Kec. Panakkukang, Makassar City, South Sulawesi 90233. In order for company management to be aligned with technology, a good IT governance is required. In this rese arch, a COBIT 2019 IT-related goal mapping of enterprise goals will be carried out. COBIT is a system for data administration and innovation and board, focused on the whole effort. The purpose of governance and management (“jobs”) is primarily as an educational resource for corporate IT governance, assurance, risk, and security professionals [1]. The stages carried out will refer to the stages of identifying IT governance, namely enterprise governance of IT, business / IT alignment, and value creation [2].